PHYSIOLOGICAL NEEDS IN JOJO MOYES’ NOVEL ME BEFORE YOU - Rika Alvionika Sari; Devi Pratiwy (Universitas Islam Sumatera Utara, 2023)
This research is aimed at protagonist’s physiological needs in the novel Me Before You written by Jojo Moyes based on Maslow’s theory. There are five basic needs based on Maslow’s theory. This study only focuses on physiological needs in the protagonist’s life. Physiological needs, the most important basic needs, is the elements needed by human being in maintaining life and health. This study used qualitative method to describe the obtained data. The result shows that there are four important points of physiological needs found in the protagonist’s life. Those are food, water, clothing and rest. It is found that the protagonist in the novel puts first her basic needs. She fulfills her needs for food, water, cloth, and rest. The basic needs must be fulfilled first before other needs. Therefore, the protagonist in the novel can live healthily and continues her life safely.